The invention of Romanal: Re-evaluating the Reputation of an Esperanto Hero - Owen, Tim (Investigationes Linguisticae, 2023)
Alfred Michaux’s is a name known to members of the Esperanto Movement who are knowledgeable about its glorious early days. Among the most prominent of the pioneers, he was a friend of the language’s creator, and the person who set up the first international congress, an annual tradition which only the two World Wars and the coronavirus pandemic have interrupted. What is generally not known about Michaux is that he ceased his activity for Esperanto within a few years, creating his own planned language, Romanal. Nor is his name associated with a damaging schism within the Esperanto Movement, the Ido Crisis, as it should be.